Biodiversity and Ecosystem Services of Agricultural Landscapes. Agroecology for Food Security and Nutrition - DeClerck, Fabrice A.J.; Estrada-Carmona, Natalia; Garbach, K.; Martínez Salinas, A. (2015)
Agriculture faces the dual challenge of feeding a 9-12 billion global population by 2050 and reducing its footprint on the environment. While the impact of agriculture on the environment is well recognized, and there are growing calls for efforts to reduce or mitigate this impact, the ecosystem services approach presents an alternative where ecosystems are managed to support and improve agriculture. As the world’s single largest terrestrial ecosystem, agro-ecosystems must be managed for the multiple goods and services they provide. A principal question for agroecology is whether the large-scale adoption of ecosystem-based approaches is capable transforming agriculture’s environmental externalities from negative to positive, while meeting food production needs. Ecosystem services science plays a significant role in this transformation by focusing attention on how biodiversity in agricultural landuses and landscapes can be managed for multiple benefits. We provide an example from the Volcanica Central Talamanca Biological Corridor in Costa Rica, where significant research has been undertaken, and is beginning to show where synergistic interactions between conservation, agricultural production and hydropower generation can be managed for multiple benefits. We recognize that significant trade-offs can exist. However, focusing attention on these multiple services, understanding their mechanisms, and quantifying the benefits of the trade-offs between the multiple services of agricultural landscapes provides novel solutions and spaces for managing positive interactions between agriculture and the environment.